PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT TERHADAP KINERJA KARYAWAN MELALUI PERILAKU PRODUKTIF KARYAWAN PADA PT. TRI TEGUH MANUNGGAL SEJATI-KAMPAR - Pasaribu Togu Satria Mathias; Daulay Nauli Iwan; Andreas Prima (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to see and determine the direct and indirect effect of the Effect of Total Quality Management Implementation on Employee Performance through Employee Productive Behavior The population in this study were all employees of PT. Tri Teguh Manunggal Sejati (TTMS) Kampar-Riau, totaling 138 people, using Path Analysis. In this study, the sampling method used the Census Technique, which is a sampling technique in which the entire population is selected to be a member of the sample so that the sample becomes 138 respondents. Total Quality Management and productive behavior have a significant effect on employee performance. For Total Quality Management has a significant effect on productive behavior. And productive behavior is able to mediate Total Quality Management and has a significant effect on employee performance. Keywords: Total Quality Management, Productive Behavior and Employee Performance